Molluscs—A ticking microbial bomb - Kijewska, Agnieszka; Koroza, Aleksandra; Grudlewska-Buda, Katarzyna; Kijewski, Tomasz; Wiktorczyk-Kapischke, Natalia; Zorena, Katarzyna; Skowron, Krzysztof (Frontiers in Microbiology, 2023)
Bivalve shellfish consumption (ark shells, clams, cockles, oysters) has increased over the last decades. Following this trend, infectious disease outbreaks associated with their consumption have been reported more frequently. Molluscs are a diverse group of organisms found wild and farmed. They are common on our tables, but unfortunately, despite their great taste, they can also pose a threat as a potential vector for numerous species of pathogenic microorganisms. Clams, in particular, might be filled with pathogens because of their filter-feeding diet. This specific way of feeding favours the accumulation of excessive amounts of pathogenic microorganisms like Vibrio spp., including Vibrio cholerae and V. parahaemolyticus, Pseudomonas aeruginosa, Escherichia coli, Arcobacter spp., and faecal coliforms, and intestinal enterococci. The problems of pathogen dissemination and disease outbreaks caused by exogenous bacteria in many geographical regions quickly became an unwanted effect of globalised food supply chains, global climate change, and natural pathogen transmission dynamics. Moreover, some pathogens like Shewanella spp., with high zoonotic potential, are spreading worldwide along with food transport. These bacteria, contained in food, are also responsible for the potential transmission of antibiotic-resistance genes to species belonging to the human microbiota. Finally, they end up in wastewater, thus colonising new areas, which enables them to introduce new antibiotic resistance genes (ARG) into the environment and extend the existing spectrum of ARGs already present in local biomes. Foodborne pathogens require modern methods of detection. Similarly, detecting ARGs is necessary to prevent resistance dissemination in new environments, thus preventing future outbreaks, which could threaten associated consumers and workers in the food processing industry.